2019
DOI: 10.1108/jwl-07-2018-0088
|View full text |Cite
|
Sign up to set email alerts
|

Understanding narrative effects

Abstract: Purpose Employee engagement has been directly linked to organizational outcomes, and at present, improving employee engagement has increasingly been a main focus for organizations. However, studies evaluating the impact of storytelling interventions on increasing the level of employee engagement are limited. Storytelling is one of the intervention methods that can provide cognitive stimulus to employees, which in turn could change their attitudes toward work including employee engagement. The purpose of this s… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
4
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
4
3
1

Relationship

0
8

Authors

Journals

citations
Cited by 10 publications
(4 citation statements)
references
References 61 publications
0
4
0
Order By: Relevance
“…Biographical approaches have also proved relevant to the study of 'how' and 'why' adults learn in professional learning contexts (e.g. West 2001;Stroobants 2005;Fillis 2015;Gustomo et al 2019), and further understanding of motivation within adult learning in higher education (e.g. Armstrong 1998).…”
Section: Biographical Approach and Methods For The Study Of Learningmentioning
confidence: 99%
“…Biographical approaches have also proved relevant to the study of 'how' and 'why' adults learn in professional learning contexts (e.g. West 2001;Stroobants 2005;Fillis 2015;Gustomo et al 2019), and further understanding of motivation within adult learning in higher education (e.g. Armstrong 1998).…”
Section: Biographical Approach and Methods For The Study Of Learningmentioning
confidence: 99%
“…The literature has also demonstrated the value of storytelling to improve organizational processes and operations (Dykes, 2019;Elias et al, 2013) and collaboration quality, socialization and adaptation of new employees (Gustomo et al, 2019;Riche et al, 2018;Sundin, Andersson, & Watt, 2018), organizational and financial success (Vora, 2019;Welbourne, 2015), innovation capabilities and new product development and dissemination (Ciriello, Richter, & Schwabe, 2017;Dessart, 2018;Mirkovski et al, 2019), organizational knowledge management (Dalkir & Wiseman, 2004;Suzuki et al, 2018) and organizational learning and growth (Hedman, Bødker, Gimpel, & Damsgaard, 2018;Welbourne, 2015). While these studies provide conceptual evidence on the value and importance of using data storytelling in the organizational context, no research has been conducted to empirically test the relationship between data storytelling competency and business performance, and this is yet to be verified empirically through hypothesis testing.…”
Section: Data Storytelling Competency and Business Performancementioning
confidence: 99%
“…Second, while prior research has suggested that data storytelling is positively associated with business performance (Adegboyega & Bahareh, 2018;Dykes, 2019;Knaflic, 2015), no research appears to have examined the relationship between data storytelling competency and business performance. Third, although conceptual work has suggested that decision-making quality may mediate the relationship between data storytelling competency and business performance (Gustomo, Febriansyah, Ginting, & Santoso, 2019;Vora, 2019), almost no empirical evidence exists to examine this relationship and its mediating role. These research gaps can be attributed to the fact that most of the work on data storytelling in business analytics practices is conceptual and has been mainly contributed by industrial reports and consultants, which generally lack both theoretical and empirical validity.…”
Section: Introductionmentioning
confidence: 99%
“…Using them can emphasize the participants’ perspective within the context of their lives, making information richer, easier to remember, and more persuasive (Aaker, 2013; Bower, 1976; DeWitt, 2019). By conveying emotion, stories can help viewers engage in and understand the subject at hand and can enable organizations to disseminate knowledge, translate knowledge into practice, and motivate viewers to take action (Gustomo et al, 2019; Lawrence et al, 2006). Using film methods can further increase the power of storytelling by appealing to a diverse audience and repositioning evaluation participants as co-creators of knowledge (Gubrium & Harper, 2013).…”
Section: Introductionmentioning
confidence: 99%